Adaptation and validation of the encoding of observations using CONSUL-MCC: A self-determination theory-based tool to observe consultations in maternity care - Joyce Kors; Veerle Duprez; Linda Martin; Corine J. Verhoeven; Ann van Hecke; Saskia M. Peerdeman; Rashmi A. Kusurkar (Elsevier, 2023)
Objective: During autonomy-supportive consultations, professionals use a need-supportive interaction style to facilitate patients' self-regulated behaviour. To improve maternity care professionals' need-supportive interactions, it is important to provide insights into their interaction style. No tool is currently available for measuring need-supportive interactions in maternity care. Therefore, the aim of this study was to adapt the COUNSEL-CCE to evaluate need-supportive interactions in maternity care and to validate their measurements. Methods: A five-step adaptation and validation process was performed based on the guideline of Sousa and Rojjanasrirat: 1) adaptation of COUNSEL-CCE by two authors independently; 2) development of a consensus-based tool: CONSUL-MCC; 3) qualitative assessment of CONSUL-MCC; 4) pilot testing of CONSUL-MCC in the target population (N = 10) and 5) psychometric testing in the target population (N = 453). Results: All indicators of the original tool remained relevant. Four items were rephrased, one indicator was added, and all examples were adapted to maternity care. The results of psychometric testing indicated good construct validity. However, the data characteristics made it impossible to prove the presumed factor structure and perform an accurate intraclass correlation. Conclusions and innovation: COUNSEL-CCE proved to be a new instrument to gain insights into professionals' interactions and be applied to maternity care.